2009
DOI: 10.1055/s-2008-1027822
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy Interpretation by an Endoscopy Nurse – a Comparative Trial

Abstract: The endoscopy nurse detected 94 % of the significant lesions seen by the physician and no clinically relevant findings were overlooked. A pre-evaluation of the capsule video by trained staff is an accurate method and might be time effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 9 publications
0
17
0
3
Order By: Relevance
“…In fact, the difference in reading time between the physicians and the nurse was significant, but small. The previous two reports demonstrated that an endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [4,9]. If a nurse could preview the capsule endoscopy video and detect significant lesions accurately, it may allow the physician to review only the predetected abnormalities and thereby greatly reduce physician reading time.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the difference in reading time between the physicians and the nurse was significant, but small. The previous two reports demonstrated that an endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [4,9]. If a nurse could preview the capsule endoscopy video and detect significant lesions accurately, it may allow the physician to review only the predetected abnormalities and thereby greatly reduce physician reading time.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 In our recent study using the capsule procedure for study of aspirin-induced small-bowel damage, the detection rates of large erosions by physicians were similar to that by the nurse, regardless of reading mode used. 7 In the present study, the detection rate by the trained nurse was similar to that of the well-trained physician and was superior to that of the physician with limited capsule experience.…”
Section: Discussionmentioning
confidence: 72%
“…In previous trials, the mean reading time of the nurses was slightly longer than that of the physicians [15,16]. However, the trained endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [12,16].…”
Section: Discussionmentioning
confidence: 87%
“…In previous trials, the mean reading time of the nurses was slightly longer than that of the physicians [15,16]. However, the trained endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [12,16]. Thus, trained nurses could pre-read the CE videos allowing the gastroenterologist only to review the marked abnormalities and to formulate medical recommendations [17,18].…”
Section: Discussionmentioning
confidence: 99%